Analysis Of The Influence Of Business Location, Price Level And Operating Hours On The Income Of Street Vendors In Kwala Bingai Village, Stabat District, Langkat Regency - Ulfa Hasibuan; Suhendi Suhendi; Rahmad Sembiring (Journal of Management, Economic, and Accounting, 2026)
This study investigated the income of street vendors (PKL) in Kwala Bingai Village, Stabat District, Langkat Regency, based on business location, price level, and operating hours. This study was conducted using quantitative methods and an associative causality research design. This study involved 100 street vendors; 80 samples were selected using the Slovin formula with a 5% error rate. Questionnaires, interviews, observations, and documentation were the data collection methods. Data quality tests and classical assumption tests were conducted before using multiple linear regression for data analysis. With a calculated F value of 7.584 and a significance of 0.000 (<0.05), the results showed that business location, price level, and operating hours had a significant influence on PKL income. With a calculated t value of 4.285 and a significance of 0.000, business location had a partial effect on income, becoming the most dominant variable. Price level had an effect on income but was not dominant, and operating hours had no effect on income with a significance of 0.412 (greater than 0.05). The coefficient of determination (R2) of 0.280 indicates that these three variables account for 28% of the variation in income, while the remaining 72% is due to factors not included in the research model. According to this study, one of the main factors in increasing street vendor income is choosing a strategic business location.